The focal complex of epithelial cells provides a signalling platform for interleukin‐8 induction in response to bacterial pathogens. (2nd June 2014) - Eucker, Tyson P.; Samuelson, Derrick R.; Hunzicker‐Dunn, Mary; Konkel, Michael E.
Summary Bacterial pathogens can induce an inflammatory response from epithelial tissues due to secretion of the pro‐inflammatory chemokine interleukin‐8 (IL‐8). Many bacterial pathogens manipulate components of the focal complex (FC) to induce signalling events in host cells. We examined the interaction of several bacterial pathogens with host cells, including Campylobacter jejuni, to determine if the FC is required for induction of chemokine signalling in response to bacterial pathogens. Our data indicate that secretion of IL‐8 is triggered by C. jejuni, Helicobacter pylori and Salmonella enterica serovar Typhimurium in response to engagement of β1 integrins. Additionally, we found that the secretion of IL‐8 from C. jejuni infected epithelial cells requires FAK, Src and paxillin, which in turn are necessary for Erk 1/2 recruitment and activation. Targeting the FC component paxillin with siRNA prevented IL‐8 secretion from cells infected with several bacterial pathogens, including C. jejuni, Helicobacter pylori, Salmonella enterica serovar Typhimurium, Staphylococcus aureus, Pseudomonas aeruginosa, and Vibrio parahaemolyticus. Our findings indicate that maximal IL‐8 secretion from epithelial cells in response to bacterial infection is dependent on the FC. Based on the commonality of the host response to bacterial pathogens, we propose that the FC is a signalling platform for an epithelial cell response to pathogenic organisms.